Questionário de Estilos e Dimensões Parentais – Versão Reduzida: Adaptação portuguesa do Parenting Styles and Dimensions Questionnaire – Short Form - Miguel, Isabel (2009)
The Parenting Styles and Dimensions Questionnaire – Short Form (Robinson, Mandleco, Olsen & Hart, 2001) is a self-report measure designed to assess the parenting styles of parents of school-age children, with good psychometric properties internationally established. Aiming to present the Portuguese version of this instrument, a sample of 344 fathers and mothers of 1st to 4th graders completed the questionnaire. Structural equation modelling procedures (confirmatory factor analysis) outlined a multidimensional and hierarchical factorial structure, similar to the original version, composed of first and second order factors, representing authoritative, authoritarian and permissive parenting styles, and corresponding dimensions. Generally, good model fit provides support to the theoretical model. Internal reliability scores were satisfactory and close to results of the original studies.